E-cigarette and hookah adoption patterns: Is the harm reduction theory just so much smoke?. (June 2020) - Ford, Eric W.; Chan, Kitty S.; Parikh, Megha; Lowe, Kevin B.; Huerta, Timothy R.
Highlights: Smoking initiation and progression patterns are changing with due to new products. E-cigarettes are potentially drawing new populations to nicotine addictive behavior. The role of cigars is changing. Flavored versions are different than prior generations' products. Abstract: Aims: This paper explores inter-generational changes in consumers smoking product uptake and use patterns after the introduction of e-cigarettes and hookahs. Design: Item Response Theory (IRT) is used to analyze the Health Information National Trends Survey sponsored by the Food and Drug Administration (HINTS-FDA). The survey was fielded in 2015. IRT allows the pattern of product use to be described and help assess whether the new tobacco products (i.e., e-cigarettes, hookahs) serve as gateway to other products or act in harm reduction modality. Findings: The results indicate that the new product alternatives have changed the how tobacco products are adopted in the U.S. In particular, younger respondents were more likely to have engaged in cigar, e-cigarette and water-pipe use than the older cohort. Conclusions: The introduction of nicotine products previously unavailable in the U.S is creating new modes for smoking initiation in the age groups most likely to begin a new habit. There is little evidence that smokers in the older HINTS cohorts are using the e-cigarette as a smoking cessation tool. The rise of cigar use in the younger cohort may indicate that legal products are being mixed with illicit substances (i.e., 'blunting').